Evaluation of the Korean version of the self-assessment of nursing informatics competencies scale - Kyoungsan Seo; Yul Ha Min; Seung-Hye Choi; Haeyoung Lee (BMC, 2019)
Abstract Background In order to assess nursing students' informatics competency, we need a comprehensive Korean version scale that reflects the important advances in nursing informatics and can make up for the lack of an existing measure. This study aimed to cross-culturally adapt the Self-Assessment of Nursing Informatics Competencies Scale (SANICS) into Korean (K-SANICS) and verify its validity and reliability with nursing students. Methods The design of this study was a methodological approach to translate and evaluate the Korean version tool (K-SANICS). A total of 254 nursing students at four universities in Korea completed a structured questionnaire including background characteristics and the K-SANICS. Reliability and validity of the 30-item K-SANICS were evaluated using Cronbach's α, content validity, factor analysis, and contrasted groups approach. Results Cronbach's α was .95. Exploratory factor analysis was performed to verify the scale's construct validity, identifying 30 items across six categories: advanced skills for clinical informatics, basic application skills, basic computer skills, roles in nursing informatics, skills for clinical applications, and attitude toward computers in nursing. Conclusion The K-SANICS may be used as a reliable assessment tool of nursing students' nursing informatics competencies. It is expected that the K-SANICS will contribute to establishing, operating, and evaluating nursing informatics curricula and also can be used in a clinical setting.